Inventory Management Models in the Supply System of Spare Parts for Military Vehicles - Kovač-Striko, Elizabeta; Spudić, Robert; Ivanković, Božidar (Promet - Traffic&Transportation, 2012)
The term inventory implies various material means whichare for a certain period of time excluded from the productionprocess or transport with the aim of being used at a later pointin time, as the need might arise.The work analyses an example of the operation method ofone system according to the model of rejecting unsatisfied demands,with the task of determining the op1imal invento1y volumeand !he ordering levels in order 10 minimise the annualcosts.